2007
DOI: 10.1210/jc.2007-0646
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Receptor Activator of Nuclear Factor-κB (RANK)/RANK Ligand/Osteoprotegerin: Clinical Implications

Abstract: The RANK/RANKL/OPG system mediates the effects of calciotropic hormones and, consequently, alterations in their ratio are key in the development of several clinical conditions. New agents with the potential to block effects of RANKL have emerged for treatment of postmenopausal osteoporosis and malignancy-related skeletal disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
175
0
10

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 231 publications
(188 citation statements)
references
References 87 publications
3
175
0
10
Order By: Relevance
“…OPG blocks the interaction between nuclear factor-kB (RANK) and its ligand (RANKL), thus inhibiting osteoclast differentiation and activity, and consequently preventing bone resorption (Bolon et al 2001). Calciotropic hormones and cytokines, including PTH, apparently act through a dual mode to inhibit OPG production and stimulate RANKL production (Vega et al 2007). Previous in vitro studies of osteoblasts have indicated that PTH either decreases (Huang et al 2004) or does not affect (Coetzee et al 2007) OPG levels.…”
Section: Discussionmentioning
confidence: 99%
“…OPG blocks the interaction between nuclear factor-kB (RANK) and its ligand (RANKL), thus inhibiting osteoclast differentiation and activity, and consequently preventing bone resorption (Bolon et al 2001). Calciotropic hormones and cytokines, including PTH, apparently act through a dual mode to inhibit OPG production and stimulate RANKL production (Vega et al 2007). Previous in vitro studies of osteoblasts have indicated that PTH either decreases (Huang et al 2004) or does not affect (Coetzee et al 2007) OPG levels.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, further studies are needed to determine if the reduction of serum RANKL levels in children may also indicate a greater risk for fracture, as was suggested for adults (35). Additionally, several factors that impair the interpretation of RANKL and OPG measurements should be considered (36). OPG is also produced in tissues such as the skin, stomach, intestine, lung, heart, and placenta.…”
Section: Discussionmentioning
confidence: 99%
“…OPG is also produced in tissues such as the skin, stomach, intestine, lung, heart, and placenta. In addition, enzymatic assays detect several fragments of circulating OPG (36). The variables that may interfere with the determination of soluble RANKL range from the instability of the molecule itself to the influence of physiological factors such as the menstrual cycle, age and gender (36).…”
Section: Discussionmentioning
confidence: 99%
“…Other rare causes of PO include idiopathic juvenile osteoporosis (IJO) [1,2], the osteoporosis-pseudoglioma syndrome, and the juvenile and early-onset Paget's disease [9].…”
Section: Causes Of Pediatric Osteoporosismentioning
confidence: 99%
“…In the case of inflammatory disorders, IL-1b and IL-6 stimulate the osteoblast to produce RANKL, stimulating bone marrow stem cells to differentiate into osteoclasts, hence increasing bone resorption [9].…”
Section: Causes Of Pediatric Osteoporosismentioning
confidence: 99%